Godfatherism and Electoral Security in Nigeria’s Fourth Republic: A Human Security Approach - Olawale Olufemi Akinrinde; Michael Atoyeje (The Republic of Indonesia Defense University, 2023)
This study delves into the intricate relationship between godfatherism and electoral politics in Nigeria's Fourth Republic, with a specific focus on the 2018 gubernatorial election in Osun State. Godfatherism has emerged as a prevalent phenomenon in Nigerian politics, where influential figures play significant roles in shaping political outcomes. Using a human security analytical approach, this study critically examines the link between godfatherism and electoral politics in Nigeria's fourth republic and its implication for human security, focusing on the micro-political analysis of the Osun state gubernatorial election in 2018. Employing a mixed-methods approach, this study draws on descriptive research methodology and the Elite theoretical framework to uncover the complexities of godfatherism and its implications for electoral politics. The findings indicate that godfatherism, despite its potential benefits for the democratic balance of power, has taken an unsettling turn in Nigeria's electoral environment, thus posing grave dangers to human security. It has evolved into a disruptive force, undermining the foundations of popular democratic governance and denying citizens the full dividends of democracy. The study highlights how godfatherism influences candidate selection, party loyalty, and electoral outcomes. Moreover, the study reveals that godfatherism perpetuates a system of political patronage, compromising the independence and accountability of elected officials. It also examines the consequences of godfatherism on the unity of political parties, electoral malpractices, and the quality of democratic representation in Osun State. In conclusion, this study underscores the need to reevaluate the role of godfatherism in Nigeria's electoral politics while advocating for reforms in the political system to promote transparency, accountability, and citizen participation.